If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -17m = -13m + -6 Reorder the terms: 18 + -17m = -6 + -13m Solving 18 + -17m = -6 + -13m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '13m' to each side of the equation. 18 + -17m + 13m = -6 + -13m + 13m Combine like terms: -17m + 13m = -4m 18 + -4m = -6 + -13m + 13m Combine like terms: -13m + 13m = 0 18 + -4m = -6 + 0 18 + -4m = -6 Add '-18' to each side of the equation. 18 + -18 + -4m = -6 + -18 Combine like terms: 18 + -18 = 0 0 + -4m = -6 + -18 -4m = -6 + -18 Combine like terms: -6 + -18 = -24 -4m = -24 Divide each side by '-4'. m = 6 Simplifying m = 6
| 3(-2x+4)=6(x+2) | | 5w-16=24 | | -y=-3y-14 | | 6x-8x+2=-3 | | -4r+11=-7r-1+3r | | 10p+8p=p+44 | | 15-3y=4x | | 6x=20(8) | | -6q-5=2q+3-10q | | r+192=-8r+3 | | 5x^2+20=5 | | 5(3x+9y)= | | 6x-8x+2=3 | | 4xy/4x=8x^2/4x | | (2x-2)+(5x-13)=90 | | 92=4u+12 | | 2p=36 | | -4f+3=-4-3f | | x-2=-23 | | .33(.2x-1)+.35x=.05(3x+7)-1.44 | | 4xy=8x^2 | | 7d-13=-13+7d | | 3-5z+1=-3-6z | | j-60=-j-4 | | m=5/3x-2 | | m/-14-4 | | |5x+10|=15 | | 4x(y)/4x=0 | | 4xy/4x=0 | | 34+x=x-2 | | 3(2h+7)= | | 1-7w=-6w-9 |